Enhancing ESL students academic writing skills through the term-paper - Rafik Galea, Shameem; Arumugam, Nalini; De Mello, Geraldine (Universiti Putra Malaysia Press, 2012)
Tertiary ESL students find writing the academic term-paper a complex process as they grapple with issues about academic writing conventions and ethics. This paper examines tertiary students’ thoughts and perceptions in co-constructing knowledge about academic writing and how multi-drafting and feedback strategies enhance their academic literacy skills through term-paper writing. In particular, we examine the use of the term-paper as a pedagogical instrument incorporating the process approach to writing for developing academic writing skills among tertiary level students in Malaysia including the importance of multi-drafting, where students reflect on the writing of the multi-drafts and evaluate their learning while working in groups. The respondents are 38 Diploma in Business Management students from a Malaysian university enrolled in an academic writing course. Focus group interviews, group observations and respondents reflective journal entries provided the qualitative data. Our findings show that group multi-drafting and feedback processes enhanced students understanding of writing as a recursive process and sharpened their academic writing literacy knowledge in the areas of referencing, planning, idea generation, editing and revising. We conclude that the multi-draft term-paper approach as a pedagogical tool seems to be a feasible solution to heightening the academic writing skills and confidence of tertiary students.